Coupled Fixed Point Problem in Abstract Convex Spaces - Park, Sehie (Journal of Informatics and Mathematical Sciences, 2020)
We establish some existence results for a generalized coupled coincidence point problem (for short, (GCCP)) in abstract convex spaces. The solvability of the GCCP is presented by using our KKM theory. Also, we derive the results on coupled coincidence points and coupled fixed points, which were studied by Lakshmikantham and Ciric, Amini-Harandi, and Mitrovic.